ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI SULAWESI TENGGARA - Inzana, Nur; Jumaah, Siti Hidayatul (Nusantara Hasana Journal, 2022)
Abstract The Secretariat of the Southeast Sulawesi Provincial DPRD is one of the agencies in which there are employees whose performance has not been achieved optimally. This failure was caused by various aspects, such as: work performance, individual, and leadership, where these three aspects are closely related to organizational culture. This research uses quantitative method with Partial Least Square (PLS) analysis technique. The sample in this study were 37 respondents who were determined by saturated sampling technique. The results showed that: (1) work motivation had a significant positive effect on employee performance, (2) work motivation did not mediate the effect of work ability and work climate on employee performance, (3) work ability had a significant positive effect on employee performance, (4) work ability has a significant effect on mediating work motivation, (5) work climate has no significant positive effect on employee performance, (6) work climate has no significant positive effect on mediating work motivation. Thus, it is concluded that organizational culture affects employee performance, so several things need to be considered, namely: 1) employees need to foster mutual trust between fellow employees, master work well, support and harmony with superiors as motivation, and 2) employees need to be transferred to a different work unit so that they have experience and provide training both in terms of leadership and in terms of communication.